Immunization of the elderly: fake news and common sense in the light of systemic theory - Maíra de Lima Silva; Maysa Kelly de Lima (Universidade de Pernambuco, 2021)
Objectives: To identify challenges in the vaccination of the elderly due to the influences of fake s news and common sense, in the light of systemic theory. Methods: This is a reflective study conceptualized in the systemic theory, neuro-endocrine immunological axis, on the challenges of vaccination of the elderly today. Results: The systemic theory emphasizes the need to stimulate the immune system of the elderly through vaccination, preventing diseases, but there is a resistance of this population to adhere to vaccination, due to fear, distrust and doubt, these uncertainties are due to the dissemination of fake news and the culture of common sense. Conclusion: The influences of fictitious information, fake news and common sense, generate challenges in immunization and reduce the adherence of the elderly, thus, health professionals are responsible for designing interventions for adherence to vaccination, demystifying wrong information.